Karakteristik Uji Proksimat dan Antioksidan Pada Olahan Nugget Ayam Kecombrang - Juanda, Dede; Aprialdi, Muhammad Agung (Universitas Djuanda, 2022)
Nuggets in its development can be made using animal raw materials other than chicken or vegetables. Referring to the Indonesian National Standard, the nutritional content in 100g of chicken nuggets, contains 60g water content, 12g protein, 20g fat content, 25g maximum carbohydrate, and 30 mg maximum calcium content. Making chicken nuggets with the addition of torch ginger will certainly bring out food innovative products that are beneficial to society. The method used in this study was experimental and proximate and antioxidant testing was carried out using the DPPH method. The nugget formula used in this study refers to Nurhamidah, U. L (2022) which has been standardized and modified and divided into 4 formulas, N0 is the control formula, N1 has the addition of 15% torch ginger, N2 has the addition of 20% torch ginger, and N3 has 25% torch ginger addition. The results of the proximate test that has been carried out show that the data contains a moisture content of 54.47s-64.51%, an ash content with susceptibility of 1.17-1.51%, a fat content of 11.06-13.44%, and a protein of 18.88-25.35%. Furthermore, the results of the antioxidant test using the DPPH method showed that the torch ginger chicken nugget had an IC50 value <50 μg/mL, namely N0 11.612, N1 unknown, N2 21.7112, N3 26.288.